Performance Comparison of Multi Input Capacitor Converter Circuits - Sreejith S; Karthik Balasubramanian (Institute of Advanced Engineering and Science, 2018)
This paper analyze the operation of a multi input switched capacitor (MIC) converters using a couple of switches, diodes and capacitors for several levels. With two input sources it is possible to obtain 8 output voltage levels. Here, 5 topologies of switched capacitor circuits namely summation, subtraction, inverting, double and half circuits are simulated and their performances are analyzed. Multi Input Converters have a high regard for multiple renewable energy sources used in smart grid systems, especially for distributed generators. The effects on output voltage with variation in load for different frequencies are also analyzed. Hardware implementation of summation and subtraction circuit is carried out and the results are compared with the simulated results